An examination of health care utilization during the COVID-19 pandemic among women with early-stage hormone receptor-positive breast cancer - Andrew J. Paladino; Kinsey Pebley; Mehmet Kocak; Rebecca A. Krukowski; Teresa M. Waters; Gregory Vidal; Lee S. Schwartzberg; Andrea N. Curry; Ilana Graetz (BMC, 2022)
Abstract Background Women undergoing treatment for breast cancer require frequent clinic visits for maintenance of therapy. With COVID-19 causing health care disruptions, it is important to learn about how this population's access to health care has changed. This study compares self-reported health care utilization and changes in factors related to health care access among women treated at a cancer center in the mid-South US before and during the pandemic. Methods Participants (N = 306) part of a longitudinal study to improve adjuvant endocrine therapy (AET) adherence completed pre-intervention baseline surveys about their health care utilization prior to AET initiation. Questions about the impact of COVID-19 were added after the pandemic started assessing financial loss and factors related to care. Participants were categorized into three time periods based on the survey completion date: (1) pre-COVID (December 2018 to March 2020), (2) early COVID (April 2020 - December 2020), and later COVID (January 2021 to June 2021). Negative binomial regression analyses used to compare health care utilization at different phases of the pandemic controlling for patient characteristics. Results Adjusted analyses indicated office visits declined from pre-COVID, with an adjusted average of 17.7 visits, to 12.1 visits during the early COVID period (p = 0.01) and 9.9 visits during the later COVID period (p < 0.01). Hospitalizations declined from an adjusted average 0.45 admissions during early COVID to 0.21 during later COVID, after vaccines became available (p = 0.05). Among COVID period participants, the proportion reporting changes/gaps in health insurance coverage increased from 9.5% participants during early-COVID to 14.8% in the later-COVID period (p = 0.05). The proportion reporting financial loss due to the pandemic was similar during both COVID periods (34.3% early- and 37.7% later-COVID, p = 0.72). The proportion of participants reporting delaying care or refilling prescriptions decreased from 15.2% in early-COVID to 4.9% in the later-COVID period (p = 0.04). Conclusion COVID-19 caused disruptions to routine health care for women with breast cancer. Patients reported having fewer office visits at the start of the pandemic that continued to decrease even after vaccines were available. Fewer patients reported delaying in-person care as the pandemic progressed.